Photophysical characterization of the 9, 10-disubstituted anthracene chromophore and its applications in triplet–triplet annihilation photon upconversion. Issue 42 (5th October 2015) - Gray, Victor; Dzebo, Damir; Lundin, Angelica; Alborzpour, Jonathan; Abrahamsson, Maria; Albinsson, Bo; Moth-Poulsen, Kasper
Abstract : Eight 9, 10-disubstituted anthracenes have been synthesized, photochemically characterized and used for triplet–triplet annihilation photon upconversion. Abstract : Molecules based on anthracene are commonly used in applications such as OLEDs and triplet–triplet annihilation upconversion. In future design of blue emitting materials it is useful to know which part of the molecule can be altered in order to obtain new physical properties without losing the inherent optical properties. We have studied the effect of substitution of 9, 10-substituted anthracenes. Eight anthracenes with aromatic phenyl and thiophene substituents were synthesised, containing both electron donating and accepting groups. The substitutions were found to affect the UV/Vis absorption only to a small extent, however the fluorescence properties were more affected with the thiophene substituents that decreased the fluorescence quantum yield from unity to <10%. DFT calculations confirm the minor change in absorption and indicate that the first and second triplet state energies are also unaffected. Finally the three most fluorescent derivatives 4-(10-phenylanthracene-9-yl)pyridine, 9-phenyl-10-(4-(trifluoromethyl)phenyl)anthracene and 4-(10-phenylanthracene-9-yl)benzonitrile were successfully utilized as annihilators in a triplet–triplet annihilation upconversion (TTA-UC) system employing platinum octaethylporphyrin as the sensitizer. The observed upconversion quantum yields, ϕ UC, slightly exceeded that of the benchmark annihilator 9, 10-diphenylanthracene (DPA).